Climate variability and changes in rainfall trends in the east coast of Peninsular Malaysia - Olaniyan, Olusegun Mayowa (2013)
The coastlines have been identified as the most vulnerable region with respect to response to hydrological hazards as a result of climate change and variability. The east coast of Peninsular Malaysia is not an exception in this regard considering the evidence of heavy rainfall resulting in floods as an annual phenomenon and also the drought that is brought about as a result of long dry spell in the region. It is envisaged that future climate changes may bring about climatic variability which may in turn produce large changes in the in the probability of occurrence of extreme hydrologic events. A study has been carried out to understand the recent trends in rainfall amount and rainfall related extreme events such as maximum daily rainfall, number of rainy days, average rainfall intensity, heavy rainfall days, extreme rainfall days, and precipitation concentration index in the east coast of Peninsular Malaysia. Long term (1971-2010) data of 40-year daily rainfall records at 55 stations along the east coast of Peninsular Malaysia have been analyzed by using non-parametric Mann-Kendall test and Sen’s slope method to understand the trends and estimate the magnitude of change. The study shows that annual rainfall, precipitation concentration index, high rainfall and extreme rainfall have increased significantly at many stations in the east coast of Peninsular Malaysia. The study concluded that the rainfall has become more distributed over the year which has reduced dry spells, however, the extreme rainfall events have increased which may be the cause of extreme hydrologic event of floods that is experienced in the region